ԱՄՆ-Իսրայել հարաբերությունների հիմնական միտումները (2009-2010 թ. առաջին կես) - Պողոսյան, Բենիամին («Զանգակ - 97»)
The Obama administration came to power with a promise to make fundamental changes in US domestic and foreign policy. Among many challenges facing new American administration was the reinvigoration of the Middle East peace process. Any serious actions in this direction would inevitably influence the US-Israel relations.
Keywords: Պատմություն; Քաղաքականություն